PARAMETERS OF GROWTH AND DEVELOPMENT OF BEES OF THE LOCAL POPULATION - Eshdavlatov Arif Zokirovich; Nurboyev Eshiniyaz Dusboyevich; Nurboyev Bakhtiyor Bakhtiyor (Scholar Express Journal, 2022)
The methods of growth and development of bee families in the local population are described in the Republic, the daily egg-laying rate of queens, the number of offspring is studied in a frame-grid of 5 × 5 cm square
Keywords: Eggs; Family; Bees; Productivity